Human Rights Protection in Interfaith Marriages: Comparative Study of Indonesia and Singapore - Muhammad Ihab Ramadhan; Safira Wijaya; Anggi Rachma Zakia Fitri; Ghea Tyagita Cahyasabrina; Bunga Cantika; Dwi Aryanti Ramadhani (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
This research aims to determine the registration of interfaith marriages in Indonesia and Singapore after the issuance of SEMA Number 2 of 2023 and the protection of human rights regarding the registration of interfaith marriages in Indonesia after the issuance of SEMA Number 2 of 2023. In Indonesia, marriage is regulated in Law Number 1 of 1974 and KHI , while in Singapore marriage is regulated in the AMLA and Women's Charters. This research uses normative legal research methods with the type of library research and uses a statutory approach and a comparative approach. The research results show that before the issuance of SEMA number 2 of 2023, the District Court can ratify applications for registering interfaith marriages. However, after the issuance of SEMA number 2, it was firmly stated that interfaith marriages may not be determined by any District Court. As for the protection of human rights for citizens regarding the registration of interfaith marriages in Indonesia after the issuance of SEMA Number 2, if it is related to human rights, Indonesia can be said to have limited the human rights of every citizen to have a family. This is different from Singapore, which facilitates interfaith marriages as regulated in the Women's Charter.